Central and peripheral chemoreceptors in sudden infant death syndrome. (19th May 2018) - Porzionato, Andrea; Macchi, Veronica; De Caro, Raffaele
Abstract: The pathogenesis of sudden infant death syndrome (SIDS) has been ascribed to an underlying biological vulnerability to stressors during a critical period of development. This paper reviews the main data in the literature supporting the role of central (e.g. retrotrapezoid nucleus, serotoninergic raphe nuclei, locus coeruleus, orexinergic neurons, ventral medullary surface, solitary tract nucleus) and peripheral (e.g. carotid body) chemoreceptors in the pathogenesis of SIDS. Clinical and experimental studies indicate that central and peripheral chemoreceptors undergo critical development during the initial postnatal period, consistent with the age range of SIDS (<1 year). Most of the risk factors for SIDS (gender, genetic factors, prematurity, hypoxic/hyperoxic stimuli, inflammation, perinatal exposure to cigarette smoke and/or substance abuse) may structurally and functionally affect the developmental plasticity of central and peripheral chemoreceptors, strongly suggesting the involvement of these structures in the pathogenesis of SIDS. Morphometric and neurochemical changes have been found in the carotid body and brainstem respiratory chemoreceptors of SIDS victims, together with functional signs of chemoreception impairment in some clinical studies. However, the methodological problems of SIDS research will have to be addressed in the future, requiring large and highly standardized case series. Up‐to‐date autopsy protocols should be produced, involving substantial, and exhaustive sampling of all potentially involved structures (including peripheral arterial chemoreceptors). Morphometric approaches should include unbiased stereological methods with three‐dimensional probes. Prospective clinical studies addressing functional tests and risk factors (including genetic traits) would probably be the gold standard, allowing markers of intrinsic or acquired vulnerability to be properly identified. Abstract : Main findings (derived from autoptic and experimental studies) supporting a role for central and peripheral chemoreceptors in the pathogenesis of SIDS.